EKSISTENSI SASTRA ANAK DALAM PEMBENTUKAN KARAKTER PADA TINGKAT PENDIDIKAN DASAR - Ayyu Subhi Farahiba (Universitas Muhammadiyah Ponorogo, 2017)
The impact of the current globalization is seen from the appearance of some of the interesting phenomenon that afflicts the young generation especially children in Indonesia. Various issues of the world educational coloring make the sublime values and behavior as if suspended. The efforts of the formation of character in children can be done one of them through literature. The approach used in this research is descriptive qualitative. This article studies focus on the role of children's literature in the formation of the child's character and learning literature relevant to children build characters learners at a basic level. Learning about the character of the discipline, honesty, responsibility, admit mistakes, religious, and others will be more effective if delivered through the story with a cast of character. Through literature, children will also be directed to think logically about the relation of causal and imagination that will correlate significantly with creativity so that the child will be able to think creatively (creative thinking) to always be productive. As a form of conveyor injects character education in literature to the students there are some efforts that could be made by educators. Educators reveal the values that are contained in the children's literature with the direct integration of the values of the characters become integrated parts of the subjects. Learning literature in primary schools can be classified into three groups, namely; learning fiction, poetry, drama and learning